The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1242/jeb.02448
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipid physiology and toxin catabolism underlie ethanol and acetic acid tolerance inDrosophila melanogaster

Abstract: SUMMARY Drosophila melanogaster has evolved the ability to tolerate and utilize high levels of ethanol and acetic acid encountered in its rotting-fruit niche. Investigation of this phenomenon has focused on ethanol catabolism, particularly by the enzyme alcohol dehydrogenase. Here we report that survival under ethanol and acetic acid stress in D. melanogasterfrom high- and low-latitude populations is an integrated consequence of toxin catabolism and alteration of physical properties of cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 83 publications
3
58
1
Order By: Relevance
“…1). Individuals may differ physiologically (e.g., detoxification capacity, stress hormones, metabolism; Maltby 1999, Montooth et al 2006 or behaviorally (e.g., boldness; Mella et al 2014). For example, individual brushtail possums (Trichosurus vulpecula) varied in measures of boldness, and boldness influenced foraging at patches with high predation risk and patches with low predation risk only when food toxins were low (Mella et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1). Individuals may differ physiologically (e.g., detoxification capacity, stress hormones, metabolism; Maltby 1999, Montooth et al 2006 or behaviorally (e.g., boldness; Mella et al 2014). For example, individual brushtail possums (Trichosurus vulpecula) varied in measures of boldness, and boldness influenced foraging at patches with high predation risk and patches with low predation risk only when food toxins were low (Mella et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that this pattern seen with the two abiotic stresses could arise from a combination of purging and a general stress-induced physiological weakening. Extensive work in a variety of animals shows longterm protein damage and impaired cellular functioning can result from heat and ethanol stress (Hoffmann and Parsons, 1991;Sorensen et al, 2003;Montooth et al, 2006). Studies in Drosophila found exposure to high heat and sublethal concentrations of ethanol alters membrane lipid composition and energy reserves (Sorensen et al, 2003;Montooth et al, 2006), which could have enduring negative effects on later life history traits such as female fecundity and male fertility (Krebs and Loeschcke, 1994;Bokor and Pecsenye, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well-known advantages as a model organism, D. melanogaster shows marked geographic variation in ethanol resistance, with populations from temperate latitudes being consistently more resistant than those from the tropics or subtropics (David and Bocquet, 1975;Cohan and Graf, 1985;David et al, 1986;Parkash et al, 1999;Montooth et al, 2006). This variation is correlated with allele frequency variation in the well-studied enzyme gene Alcohol dehydrogenase (Adh), whose product converts ethanol to acetaldehyde ( Fig.…”
Section: Research Articlementioning
confidence: 99%
“…Another relevant observation is that, both among D. melanogaster strains and among Drosophila species, resistance to ethanol is strongly correlated with resistance to acetic acid (Chakir et al, 1993;Eisses and Den Boer, 1995;Montooth et al, 2006). This could be explained in at least three ways.…”
Section: Research Articlementioning
confidence: 99%